Healing Potential of Senna Alata Leaves Extract in Rats - Sri Lestari Ramadhani Nasution; Monica Putri; Welpin Hulu; Ermi Girsang; Ali Napiah Nasution (Kazimierz Wielki University, 2019)
Burns known as damaged tissue which caused by contact with hot sources, such as water, fire, chemicals, electricity, and radiation. It has impact not only to skin damage but also to the whole body system. Senna Alata (Cassia alata L) is considered as herbal medicine with spicy and warm taste which believed could heal itching, skin damage and others. This study aimed to analyze the optimization of Senna Alata leaves extract in healing burn. Thirty Wistar rats or Rattusnorvigicus were used as the sample. Those Wistar rats were divided into 6 groups with 5 rats in each group which treated differently. Group 1 was negative control which given no treatment at all, group 2 was treated with bioplacenton cream, while the rest of the groups were treated using Senna Alata leaves extraction cream with different concentration; 25% for group 3, 50% for group 4, 60% for group 5, and 95% of extraction cream for group 6. This study used experimental research as the methodology using ANOVA and Tukey test. The result showed that healing potential of Senna Alata's leaves extract had significant effect in healing burn.